First Records of Black Widow Spider Latrodectus Walckenaer (Araneae: Theridiidae) in Oman - Al-Jahdhami, Ali; Al-Raeesi, Ali; Al-Rashdi, Said (EntomoBrasilis, 2022)
The present communication deals with a faunistic study on two species of Latrodectus Walckenaer with medically important issues from Oman. Several specimens of Latrodectus have been collected at various localities in Sultanate of Oman. This study records two species of Latrodectus from Oman, of which Latrodectus cinctus Blackwall only from northern Oman and Latrodectus geometricus C.L. Koch from both northern and southern Oman.